sigma*-aromaticity of substituted 1H-phosphirenium cations and substituted silacyclopropenes - Göller, Andreas H.; Clark, Timothy; et al. (Journal of Organic Chemistry, 1996)
The influence of the electronegativity of the ligands Y (F, Cl, Br, I, OH, NH2, CH3, H) on the strength of the sigma*-aromatic effect in gem-disubstituted 1H-Phosphirenium cations and substituted 3-silacyclopropenes has been investigated with ab initio theory. Phosphorus and silicon provide a low lying p-type sigma*-orbital antibonding to the ligands Y. This interacts with the ring double bond analogously to a third p-orbital in a 2 pi Huckel system. These systems have bean compared to the analogous saturated rings. Calculations at the RHF/6-31G* and MP4/6-31+G* levels, NBO analyses of the effect of the ligands Y and comparisons of the relative stabilities of the saturated and unsaturated compounds suggest a weak but significant sigma*-aromatic effect dependent on the electronegativity of Y.